Evaluation of Phosphorus Site Assessment Tools: Lessons from the USA. Issue 6 (1st November 2017) - Sharpley, Andrew; Kleinman, Peter; Baffaut, Claire; Beegle, Doug; Bolster, Carl; Collick, Amy; Easton, Zachary; Lory, John; Nelson, Nathan; Osmond, Deanna; Radcliffe, David; Veith, Tamie; et al.
Abstract : Critical source area identification through phosphorus (P) site assessment is a fundamental part of modern nutrient management planning in the United States, yet there has been only sparse testing of the many versions of the P Index that now exist. Each P site assessment tool was developed to be applicable across a range of field conditions found in a given geographic area, making evaluation extremely difficult. In general, evaluation with in‐field monitoring data has been limited, focusing primarily on corroborating manure and fertilizer "source" factors. Thus, a multiregional effort (Chesapeake Bay, Heartland, and Southern States) was undertaken to evaluate P Indices using a combination of limited field data, as well as output from simulation models (i.e., Agricultural Policy Environmental eXtender, Annual P Loss Estimator, Soil and Water Assessment Tool [SWAT], and Texas Best Management Practice Evaluation Tool [TBET]) to compare against P Index ratings. These comparisons show promise for advancing the weighting and formulation of qualitative P Index components but require careful vetting of the simulation models. Differences among regional conclusions highlight model strengths and weaknesses. For example, the Southern States region found that, although models could simulate the effects of nutrient management on P runoff, they often more accurately predicted hydrology than total P loads. Furthermore, SWAT and TBET overpredicted particulate P and underpredicted dissolved P, resulting in correct total P predictions but for the wrong reasons. Experience in the United States supports expanded regional approaches to P site assessment, assuming closely coordinated efforts that engage science, policy, and implementation communities, but limited scientific validity exists for uniform national P site assessment tools at the present time. Core Ideas: Concern over the accuracy of P Indices has led to calls for their evaluation. Insufficient field data exist to evaluate P site assessment tools comprehensively. Researchers can use nonpoint source models as surrogates to field data if vetted first. There is no scientific justification for a single national P Index.